Clarifying the origin of second-harmonic generation from an epsilon-near-zero flim-coupled plasmonic nanoparticle-on-mirror system by size-dependence properties - Zhang Yunfei; Gao Fuhua; Yang Fan (EPJ Applied Metamaterials, 2024)
We conduct a comprehensive numerical investigation on the size-dependence properties of second harmonic generation (SHG) from an epsilon-near-zero (ENZ) film-coupled plasmonic nanoparticle on-mirror (NPoM) system. The distinct size dependence of gold and indium-tin-oxide (ITO) leads to the existence of a critical point where the SHGs from these two materials are balanced. This study offers valuable guidance in the design of plasmonic systems containing ENZ materials for enhancing SHG.